2021
DOI: 10.1002/asna.202113975
|View full text |Cite
|
Sign up to set email alerts
|

The symbiotic binary ZZ CMi: Intranight variability and suggested outbursting nature

Abstract: We present photometric and spectral observations of the symbiotic star ZZ CMi.We detect intranight variability-flickering and smooth variations in U band.The amplitude of the flickering is about 0.10 − 0.20 mag in U band. In the B band, the variability is lower, with amplitude ≤ 0.03 mag. We also detect variability in the H𝛼 and H𝛽 emission lines, and find an indication for outflow with velocity of about 120-150 km/s. The results indicate that ZZ CMi is an accretion-powered symbiotic containing an M4-M6 III … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Ground-based observations in the B filter by Zamanov et al (2016a) revealed a flickering amplitude of 0.08 mag in February 2016. Subsequent observations from January to August 2023 detected variability in the range of 0.11-0.26 mag (Shore & Teyssier 2023;Minev et al 2023;Zamanov et al 2023a). This observed variability aligns broadly with the anticipated B amplitudes inferred from the TESS observations.…”
Section: Detection Of Flickering With Tesssupporting
confidence: 56%
See 1 more Smart Citation
“…Ground-based observations in the B filter by Zamanov et al (2016a) revealed a flickering amplitude of 0.08 mag in February 2016. Subsequent observations from January to August 2023 detected variability in the range of 0.11-0.26 mag (Shore & Teyssier 2023;Minev et al 2023;Zamanov et al 2023a). This observed variability aligns broadly with the anticipated B amplitudes inferred from the TESS observations.…”
Section: Detection Of Flickering With Tesssupporting
confidence: 56%
“…The challenge lies in the small amplitude of optical flickering and the limitations of relatively small ground-based telescopes used for such searches. Furthermore, even in cases where flickering is undoubtedly detected, it may not be present at all epochs (e.g., Lucy et al 2020;Georgiev et al 2022;Zamanov et al 2023b;Pujol et al 2023). Therefore, it is necessary to obtain observations over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, while large amplitude flickering has always been the rule for MWC 560 (eg. Lucy et al 2020), it has disappeared altogether during the last couple of years (Zamanov et al 2019).…”
Section: Optical Flickeringmentioning
confidence: 99%
“…This prompted a flurry of observations across the electromagnetic spectrum, from very high energy TeV/GeV γ-rays detected by H.E.S.S. 3 (Wagner 2021a,b;Aharonian et al 2022) and MAGIC 4 (Acciari et al 2022), and MeV γrays by Fermi-LAT 5 (Cheung et al 2021a(Cheung et al ,b, 2022; to X-rays seen by MAXI 6 (Shidatsu et al 2021), INTE-GRAL 7 (Ferrigno et al 2021), NICER 8 (Enoto et al 2021a,b;Luna et al 2021;Orio et al 2021b,c), NuS-TAR 9 (Luna et al 2021), AstroSat (Rout et al 2021), Chandra and XMM-Newton (Orio et al 2021a), as well as Swift (Page, Osborne & Aydi 2021;Page 2021a,b); to optical (Taguchi, Ueta & Isogai 2021;Munari & Valisa 2021a;Mikolajewska et al 2021;Munari & Valisa 2021b;Nikolov & Luna 2021;Shore et al 2021a;Shore, Teyssier & Thizy 2021;Shore et al 2021b;Munari, Valisa & Ochner 2021;Fajrin et al 2021;Ricra, Vannini & Baella 2021;Zamanov et al 2021); infrared (Woodward et al 2021a,b); and radio (Williams et al 2021;Sokolovsky et al 2021;Peters et al 2021). A neutrino search was performed by IceCube, though only upper limits could be placed (Pizzuto, Vandenbroucke & Santander 2021).…”
Section: Introductionmentioning
confidence: 99%